(untitled) (Journal of Special Education and Rehabilitation, 2014)
Background: in Germany we may state that despite all efforts of inclusive education there is a tendency towards segregated education as far as “Emotional and Social Development” is concerned. In Berlin, the “Transition” project could be developed. By the help of this support approach it was possible all participating children to stay at their primary schools. Aims: the survey was meant to find out in which way the support, in context of the “Transition” project, has contributed to successful inclusive learning of students with considerable problems in their social behaviour. Methods:a semi-standardized questionnaire for interviewing class teachers of regular school classes was used, and furthermore school certificates were assessed concerning regular school attendance as well as performance in Mathematics and German. Nine Berlin schools took part in the survey. The response rate was 96%. Results: the current survey shows that inclusive education in case of considerable problems in social behaviour may be successful by counselling parents and teachers, by cooperation with school and by youth aid, as well as by way of a temporary learning group relieving both students with difficult behaviour as well as the overall group and the teachers, one succeeds with practicing recognition and acceptance, even despite serious behavioural problems at school. Conclusion: the results clearly show that the teacher - student interaction and the student - student interaction improves significantly in the subjective perception of class teachers. For this relationship to work, all those participating in it need “a specific environment”.